Asset Stripping, Rule of Law and Firm Survival: The Hoff-Stiglitz Model and Mass Privatization in Montenegro - Matja Koman; Milan Lakičević; Janez Pranikar; Jan Svejnar (Institute for the Study of Labor (IZA), 2013)
We provide the first test of the Hoff and Stiglitz (2004) model predicting whether and under what conditions mass privatizations are accompanied by asset stripping. In addition to directly testing the theory, we also tackle an important policy-oriented issue of why a large number of efficient firms disappeared during mass privatization in a booming economy of Montenegro. Econometrically, we present the first study to look at firms that disappeared during a mass privatization transition, improving upon prior studies that focused only on existing firms and assumed away survival bias. Our analysis suggests that asset stripping and firm disappearance were present, and that asset stripping was a likely reason for the loss of efficient firms. We show that because more productive firms were liquidated, it is important to model survival bias in the selection of firms remaining in samples when estimating the effects of privatization or other ownership changes. We also show that one needs to distinguish between true start-ups and liquidated firms that re-appear as start-ups. In the absence of the rule of law, many firms that appear to have disappeared were in fact appropriated by managers and politically connected individuals.
Keywords: L33; P24; P31; 330; comparison of public and private enterprises; socialist systems and transitional economies; socialist enterprises and their transitions